2010
DOI: 10.1038/nature09373
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint-dependent inhibition of DNA replication initiation by Sld3 and Dbf4 phosphorylation

Abstract: SummaryThe initiation of eukaryotic DNA replication is regulated by three protein kinase classes: cyclin dependent kinases (CDK), Dbf4-dependent kinase (DDK) and the DNA damage checkpoint kinases1. CDK phosphorylation of two key initiation factors, Sld2 and Sld3, promotes essential interactions with Dpb112-4 whilst DDK acts by phosphorylating subunits of the Mcm2-7 helicase5. CDK plays an additional role in replication by preventing the re-loading of Mcm2-7 during S, G2 and M phases6, thus preventing origin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
309
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(333 citation statements)
references
References 30 publications
21
309
3
Order By: Relevance
“…Moreover, the Treslin -TopBP1 interaction is reduced in cells treated with hydroxyurea in a checkpoint kinase 1 (Chk1)-dependent manner (Boos et al 2011). This is reminiscent of the situation in which the Rad53 checkpoint kinase phosphorylates Sld3 to inhibit initiation by disrupting the Sld3 -Dpb11 interaction in budding yeast (Lopez-Mosqueda et al 2010;Zegerman and Diffley 2010).…”
Section: Treslin/ticrrmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Treslin -TopBP1 interaction is reduced in cells treated with hydroxyurea in a checkpoint kinase 1 (Chk1)-dependent manner (Boos et al 2011). This is reminiscent of the situation in which the Rad53 checkpoint kinase phosphorylates Sld3 to inhibit initiation by disrupting the Sld3 -Dpb11 interaction in budding yeast (Lopez-Mosqueda et al 2010;Zegerman and Diffley 2010).…”
Section: Treslin/ticrrmentioning
confidence: 99%
“…Under such conditions, further activation of unfired origins is inhibited (Painter and Young 1980;Santocanale and Diffley 1998;Shirahige et al 1998;Larner et al 1999). Studies using budding yeast showed that the checkpoint kinase Rad53 inhibits both the CDK-and DDK-dependent pathways, which are essential for the initiation of replication, by phosphorylating Sld3 and Dbf4, respectively (Lopez-Mosqueda et al 2010;Zegerman and Diffley 2010). Human Treslin/Ticrr, a functional homolog of Sld3, is also inhibited by the phosphorylation checkpoint kinase Chk1 when cells are exposed to DNAreplication stress (Boos et al 2011).…”
Section: Regulatory Aspects Of the Formation Of The Pre-icmentioning
confidence: 99%
“…As described under "Materials and Methods," G 1 -arrested cells were released into media containing 20 M CPT or 0.033% MMS. MMS is known to activate the intra-S-phase checkpoint by interfering with progression of replication fork progression (14,47,48), whereas CTP fails to do so (42). DNA was purified from the samples taken at regular (20 or 30 min) intervals after release.…”
Section: Unimpeded S-phase Progression Is Observed In Dna2⌬405n Follomentioning
confidence: 99%
“…One of the binding partners of FHA1 is Dbf4 (4), the regulatory subunit of the initiator kinase Cdc7 (5,6). The association of Rad53 and Dbf4 mediates the Rad53-dependent phosphorylation of Dbf4 and the consequent inhibition of Cdc7, thus preventing late origin firing (7)(8)(9)(10). This interaction involves the N-terminal region of Dbf4 that folds as a modified BRCA1 C-terminal (BRCT) domain (4,(11)(12)(13).…”
mentioning
confidence: 99%